KONTRIBUSI USAHA TANI JAGUNG TERHADAP PENDAPATAN KELUARGA DI DESA MOTILANGO KECAMATAN TIBAWA KABUPATEN GORONTALO - Nur Eng Mokodompit; Apris Ara Tilome; Since Mama (Universitas Muhammadiyah Gorontalo, 2023)
Indonesia is an agricultural country, meaning that agriculture plays an important role in the Indonesia is an agricultural country, meaning that agriculture plays an important role in national economic activity. This can be shown from the number of residents or workers who live or work in the agricultural sector or national products originating from agriculture. The purpose of research was to determine the contribution of corn farming to family income in Motilango Village, Tibawa District, Gorontalo Regency. The research approach used in this research is qualitative, the design used is descriptive data. The independent variable is Corn Farming Contribution while the dependent variable is family income. Based on the results of the analysis, it was found that on average, corn farmers also in their work for a long time, thus they already know marketing tactics, although many of them only reach elementary school. Conclusion was corn is very contributing to family income in Motilango Village, Tibawa District, Gorontalo Regency.